Situation of Physical Development 4-5 Years old Preschoolers in Hanoi City, Vietnam - Yen, Nguyen Thi (International Journal of Humanities and Education Development (IJHED), 2023)
In the education system, preschool is the first level of education that lays the foundation for physical, intellectual, emotional, and aesthetic development, and orients the formation of children's personalities; at the same time promoting the learning and development process in the next stages. Recognizing this importance, the Party and State have constantly paid attention to investing in facilities and quality for this level of education. However, the height growth rate of Vietnamese people is still slower than in other countries in the world and the region. Therefore, in addition to proper nutrition, preschools across the country need to develop many methods that have a profound impact on cognition to improve children's physical health. In this study, the author will focus on assessing the status of physical education at 4-5 years old preschool in Hanoi City, Vietnam. On that basis, specific goals are discussed for the research subjects, to contribute to improving the physical health of 4-5-year-old preschool in the coming time in Hanoi city.